“She said that I was a pattern-breaker”: Career aspirations and challenges for students of a transnational background in teacher education in Denmark - Benediktsson, Artëm Ingmar (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This article explores the career aspirations and educational experiences of Danish-born students of a transnational background who are nearing completion of their studies to become professional teachers in compulsory schools in Denmark. The theoretical framework of the study is grounded in the tenets of critical multiculturalism and transnationalism. The findings obtained from individual qualitative interviews with seven students indicate their overall satisfaction with teacher educators and the learning environments within their campuses. However, the participants also reported experiencing varying degrees of unfair treatment, labelling, and prejudice. Despite having encountered different forms of discrimination, the participants have ambitious career aspirations, often manifested in their determination to challenge social injustice and bring positive change to the compulsory education system.